Inequality and vulnerability of informal employment during the pandemic (Construction Economics and Building, 2023)
This study explores the impact of the COVID-19 pandemic on formal and informal workers in the Indonesian construction industry. Based on a questionnaire survey of workers in the province of West Java, it aims to test the view that informal workers are more vulnerable to job losses, wage cuts and the lack of social security safety net. Two research questions were posed. The first was to characterise the impact of the COVID preventative measures on their access to work, work hours, and income levels. The second objective was to examine the implementation of COVID-19 health and safety protocols at project sites and its impact on workers. A survey conducted in November and December 2020 in the province of West Java obtained 261 responses from 21 construction companies. Contingency table testing was carried out to test the hypothesis that the frequencies of occurrence in the formal and informal worker categories are independent of the frequencies in incomes and health and safety protocols. Contrary to job losses and wage cuts report in the literature, construction companies in West Java have resisted cutting the wages of informal workers and instead directed wage cuts to their higher paid formal workers. Compliance to COVID-19 health and safety protocols at project sites was reported to be high. This study makes unique contribution to the understanding of informal work in the construction industry and the impact of the recent pandemic on the incomes and workers’ welfare.